Elevated level of glycated KQTALVELVK peptide of albumin is associated with the risk of diabetic nephropathy - Chaurasiya, Arvindkumar H.; Jaiswal, Meera R.; Bayatigeri, Santhakumari; Kahar, Shweta; Tiwari, Shalbha; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2023)
Diabetic nephropathyis a leading cause of end-stagerenal disease.Hence, early detection of diabetic nephropathy is essential to mitigatethe disease burden. Microalbuminuria, the currently used diagnosticmarker of diabetic nephropathy, is not efficient in detecting it atan early stage. Therefore, we explored the utility of glycated humanserum albumin (HSA) peptides for risk prediction of diabetic nephropathy.Three glycation-sensitive HSA peptides, namely, FKDLG-EENFK,KQTAL-VELVK, and KVPQVST-PTLVEVSR, with deoxyfructosyllysine(DFL) modification were quantified by targeted mass spectrometry (MS)in a study population comprising healthy and type II diabetes subjectswith and without nephropathy. Mass spectrometry, receiver operatingcharacteristic (ROC) curve, and correlation analysis revealed thatthe DFL-modified KQTALVELVK peptide was better than other glycatedHSA peptides and HbA(1c) for identifying diabetic nephropathy.DFL-modified KQTALVELVK could be a potential marker for risk predictionof diabetic nephropathy.